CSR as a tool of building the competitiveness of businesses - Maja Żychlewicz (Foundations of Management, 2014)
In this article, author analyzes the application of CSR as a tool of building the competitiveness of business. She assumes that corporate social responsibility (CSR) could be a useful tool in giving a competitive edge to an enterprise.The idea of CSR as a part of the tool creating the position of the company in the market is explored by the author. Besides, an attempt to define and comprehend CSR is undertaken. The author explains the necessary requirements that must be fulfilled for CSR to play the role of a useful tool for creating the competitive edge and spheres of activity for the individual, which should be taken into consideration while creating strategic CSR.
Keywords: 650; CSR; strategy of CSR; competitiveness of enterprise; area CSR